2020
DOI: 10.3390/ma13112507
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Properties Evaluation of Cellulose Nanocrystals Cement Paste

Abstract: Due to the need for high-performance and sustainable building materials, the investigation of the determination of fracture toughness of cement paste using new and sustainable materials, such as cellulose nanocrystals (CNCs) is worthwhile. Contrary to other well-known nano-reinforcement particles, such as carbon nanotubes, CNCs are less toxic; therefore, they have less safety and environmental risks. Fracture behavior of cement paste has been studied intensively for a long time. However, the incorporation of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(29 citation statements)
references
References 18 publications
0
28
0
1
Order By: Relevance
“…Polymer fibers are the most frequently used group of fibers as reinforcing additives [ 25 ]. The main objective of the addition of these types of fibers is improving mechanical properties, in particular bending strength [ 24 , 27 ], and reducing the propagation of microcracks in materials [ 23 , 28 ]. Other benefits that can be achieved as a result of introducing chemical fibers into geopolymers, depending on their type, may include an increase in fire resistance [ 24 , 27 ] or a decrease in the thermal conductivity coefficient.…”
Section: Introductionmentioning
confidence: 99%
“…Polymer fibers are the most frequently used group of fibers as reinforcing additives [ 25 ]. The main objective of the addition of these types of fibers is improving mechanical properties, in particular bending strength [ 24 , 27 ], and reducing the propagation of microcracks in materials [ 23 , 28 ]. Other benefits that can be achieved as a result of introducing chemical fibers into geopolymers, depending on their type, may include an increase in fire resistance [ 24 , 27 ] or a decrease in the thermal conductivity coefficient.…”
Section: Introductionmentioning
confidence: 99%
“…Similar conclusions were obtained by Flores et al who indicated that even if the size of CNCs used is larger than that used by Cao et al [ 50 ], the overall trend in the hydration heat is similar to each other, and CNCs were observed to delay cement hydration at an early age but improve the hydration at a later age [ 24 ]. Besides, Ghahari et al indicated that the use of 0.2% and 1% CNCs by volume of cement paste could extend the dormant period of cement hydration that is indicative of the delayed hydration but increase the hydration heat that is indicative of the increased degree of hydration [ 51 ].…”
Section: Application Of Nanocellulose In Cementitious Materialsmentioning
confidence: 99%
“…Several conclusions can be drawn. First, a modest dosage of CNCs (e.g., 0.2% by weight of cement) can improve the mechanical properties, whereas a high dosage of CNCs can result in a negative effect [ 13 , 15 , 49 , 50 , 51 , 53 , 54 ]. The improvement in the mechanical properties of cementitious materials at low dosages of CNCs can be attributed to the increased degree of hydration at a given age.…”
Section: Application Of Nanocellulose In Cementitious Materialsmentioning
confidence: 99%
“…Another approach is by partial substitution of ordinary Portland cement (OPC) with waste supplementary cementitious materials (SCMs), which were categorized according to Liew et al [ 32 ] in three groups: 1—industrial wastes such as ground granulated blast furnace slag (GGBFS), fly ash (FA), and silica fume (SF), 2—agricultural wastes such as RHA, corncob ash (CA), and sawdust ash (SA), and 3—municipal wastes such as glass and plastics. Furthermore, cellulose nanocrystals are other green materials extracted from plants and trees, which when partially substituted by OPC can cause a significant reduction in CO 2 consumption with improved compressive strength and fracture properties of concrete [ 33 ].…”
Section: Introductionmentioning
confidence: 99%